Pinanga gruezoi (Arecaceae), a new slender clustering palm from the Philippines with notes on an amended description of P. samarana - Adorador, Jiro T.; Meneses, Zhereeleen D.; Fernando, Edwino S. (Phytotaxa, 2020)
We describe a new species of Pinanga, P. gruezoi, from the islands of Samar, Bucas Grande, Dinagat, and (northeastern) Mindanao, Philippines. It is a diminutive slender clustering palm with pluricostulate coriaceous leaflets, rather few, short and arching to reflexed rachillae, which bear relatively large distichously arranged and closely-set ovoid-ellipsoidal fruits. Additionally, we rediscovered P. samarana, hitherto known from type material that was first collected more than a century ago, and provided an amended description based on recent collections and field observations. Discussions on their morphology, habitat, distribution, ecology, conservation status, and comparisons with putatively closest congeners are included. Furthermore, we herein provided a tentative key for the functional groups of Philippine Pinanga and for the two species described.